Bioactive constituents of melicope bonwickii and m. lunu-ankeda (rutaceae). - Mohd. Hashim , Najihah; Komala, Ismiarni; Rahmani, Mawardi; Ee, Gwendoline Cheng Lian; Mohd Ismail, Hazar; Sukari, Mohd Aspollah; Rahmat, Asmah (2005)
The used of natural products from plant source with therapeutic properties is ancient as human civilization. Currently about 25% of modern drugs prescribed worldwide come from plants and 121 such active compounds are being used. Of the 252 drugs considered as basic and essential by World Health Organization (WHO), 11% are exclusively of plants origin and a significant number are synthetic drugs obtained from natural precursors. Deatiled phytochemical study of Melicope bonwickii (F. Muell) T. Hartley revealed the presence of four furoquinoline alkaloids in which one is a rare new chlorine-containing compound, 7(2',-hydroxy-3'-chloroprenyloxy)-4-methoxyfuroquinoline, three known alkaloids 7-(2',3'-epoxyprenyloxy)-4-methoxyfuroquinoline, evellerine and kokusaginine together with a known dipeptide, aurantiamide acetate. From leaves of Melicope lunu-ankeda (Geartn) T. Hartley, two phenylpropanoid derivatives,p-)-geranylcoumaric acid and sesamin, a quinolone alkaloid and a flavanoid were isolated and identified. The ectracts and the isolated compounds were evaluated for their antioxidant, cytotoxity and antimicrobial activities. The new furoquinoline alkaloid and 7-(2',3'-epoxyprenyloxy)-4-methoxyfuroquinoline exhibited significant cytotoxic activity against cervical cancer (Hela) cell line with IC50 values were found to be 6.0 and 11.4 µg/ml, respectively.